2022
DOI: 10.3389/fpsyg.2022.1060042
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of carbon performance and technological innovation on corporate financial performance

Abstract: In order to further implement the goal of “dual carbon” proposed by China’s government, and promote energy enterprises to carry out low-carbon economic transformation, this paper takes listed companies in China’s A-share energy industry from 2014 to 2019 as samples to conduct descriptive statistics, correlation test and regression analysis, and empirically studies the impact of carbon performance and technological innovation on financial performance of China’s energy industry as well as their roles under diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, not all enterprises or regions are willing to participate in CDP projects, and China's carbon information disclosure system is not yet perfect, so there are not many enterprises that disclose carbon emission information, and the disclosure standards are different, resulting in the inability to directly obtain standardized and unified corporate carbon emission data. Therefore, most scholars use the main business income of enterprises and operating costs to estimate the proportion of carbon emissions of enterprises from the carbon emissions of industries to measure the level of CP (Busch and Lewandowski, 2016;Yan et al, 2022).…”
Section: Measurement Of Cpmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all enterprises or regions are willing to participate in CDP projects, and China's carbon information disclosure system is not yet perfect, so there are not many enterprises that disclose carbon emission information, and the disclosure standards are different, resulting in the inability to directly obtain standardized and unified corporate carbon emission data. Therefore, most scholars use the main business income of enterprises and operating costs to estimate the proportion of carbon emissions of enterprises from the carbon emissions of industries to measure the level of CP (Busch and Lewandowski, 2016;Yan et al, 2022).…”
Section: Measurement Of Cpmentioning
confidence: 99%
“…They found that good environmental protection behaviors had a significant and positive impact on corporate FP in both developed and developing countries (Sergio and Martí-Ballester, 2017). Yan takes energy enterprises listed in China's A-shares as samples and finds that good CP and technological innovation in the energy industry have A positive impact on the FP of enterprises (Yan et al, 2022).…”
Section: The Relationship Between Cp and Fpmentioning
confidence: 99%